Strategi Pemasaran Digital dalam Meningkatkan Pendapatan Pabrik Tahu di Kelurahan Bambu Apus Kecamatan Pamulang Kota Tangerang Selatan - Silvia Sari; Rini Septiowati; Purwatiningsih Purwatiningsih; Widayat Widayat; Ruruh Dyatmiko (Universitas Pamulang, 2021)
Community Service entitled Digital Marketing Strategy in Increasing Tofu Factory Income in Bambu Apus Village, Pamulang District, South Tangerang City aims to provide knowledge about marketing strategies both offline and digitally online marketing, especially e-commerce with the background of restrictions on social interaction and working rules from home due to the Covid-19 pandemic. The implementation of this Community Service is carried out using the lecture, tutorial and discussion methods. The target of this service is all members of workers, employees and business owners of tofu factories in Bambu Apus Village. The results of this PKM have proven that business actors can master the way of selling through e-commerce in order to increase their business income.